Natural Antimicrobial Monoterpenes as Potential Therapeutic Agents in Vaginal Infections: A Review - Preeti Singh; Satish Sardana; Shiv Kr Yadav; Navidha Aggarwal; Hitesh Chopra; Kuldeep Dhama (Journal of Pure and Applied Microbiology, 2024)
The recurrence and relapse of vaginal infections in women is a major issue and a challenging pathway to identify and develop new approaches to treatment. In the case of antibiotic therapy, contraceptives, and dietary changes, the recurrence of vaginitis is more common these days. Anaerobic bacteria, Candida spp., and trichomonas in the vaginal microflora cause both symptomatic and asymptomatic vaginitis, which includes vaginal inflammation. It changes the vaginal microbiota and decreases Lactobacilli spp. growth, which is maintaining the vaginal pH (3.5-4.5) through lactic acid production, antimicrobial peptides, bacteriocin, and bacteriocin-like inhibitory substances. The remarkable antimicrobial activity of plant’s producing metabolites like alkaloids, tannins, phenolic compounds, flavonoids and terpenoids for several vaginal infections have been reported in previous studies. Presented review focuses on the pivotal role of monoterpenes, providing a detailed description of thymol, geraniol, limonene, eugenol, eucalyptol, and α-terpineol as antimicrobial molecules in the treatment of vaginal infections. These monoterpenes are very good at killing E. coli, Staphylococcus aureus, Pseudomonas aeruginosa, Aspergillus niger, Trichomonas vaginalis and Candida albicans which are the main microbes that cause vaginitis. Future research could explore the latent combinations of such monoterpenes as synergistic antimicrobial agents to treat bacterial and fungal vaginal infections, trichomoniasis, among other conditions.